112 Modulating Effects of Miscanthus Grass and Prebiotic Blends on Canine Fecal Microbiota, Metabolites, and Digestibility. (8th October 2021) - Finet, Shannon E; He, Fei; Clark, Lindsay V; de Godoy, Maria R
Abstract: Dietary fiber plays an important role in gastrointestinal health as it modulates the gut environment and promotes microbiome homeostasis. However, dietary fiber sources vary in composition, physico-chemical properties, and physiological effects. The objective of this study was to evaluate the effects of miscanthus grass fiber and prebiotic fiber blends on fecal microbiota, fecal metabolites, and apparent total tract digestibility in comparison to traditional dietary fiber sources. Animal procedures were approved by the University of Illinois Institutional Animal Care and Use Committee. Six dietary treatments were formulated to meet or exceed AAFCO nutrient profile (2018) and included either cellulose, beet pulp, miscanthus fiber, or a blend of miscanthus fiber and tomato pomace, miscanthus fiber and resistant starch, or miscanthus fiber and fructooligosaccharide. Twelve female adult beagles were randomly assigned one of the six treatments in a replicated 6x6 Latin square design and fed for 21 d including 17 d of diet adaptation followed by 4 d of total and fresh fecal collection. All diets were well digested by the animals. Dogs fed beet pulp had greater fecal total short-chain fatty acid concentration than the cellulose treatment (P < 0.05), while the dogs fed diets containing miscanthus fiber were intermediate. No difference in the α-diversity of fecal microbial communities was observed among treatments (P >0.05), while β-diversity of dogs fed the beet pulp treatment differed from the other treatment groups. Miscanthus grass can be utilized successfully in diets for adult dogs with tomato pomace and resistant starch blends resulting in similar physiological effects to cellulose.